Efeitos de diferentes fontes de lipídeos sobre as características de carcaça, perfil lipídico e proteoma do Longissimus Dorsi De cordeiros deslanados - Arruda, Paulo Cesar Lopes de (2014)
The study was conducted to evaluate the influence of supplementation of different lipid sources on performance and quantitative characteristics of housing and not housing, fatty acid profile and muscle proteome Longissimus dorsi of Santa Ines lambs fed different additional sources of lipids. 35 lambs bulls were used, with initial body weight (13 ± 1.80 kg) and approximately two months in a randomized block design with five treatments and seven repetitions. The treatments consisted of five diets, one free additional lipids (control) and the other, added cottonseed (CA), bran cashew (FCC), cottonseed with cashew nut meal (CALFCC) and calcium salts of long chain fatty acids (LCFA-Ca). The duration of the experiment was determined by the time required for the average body weight of all animals in each treatment were 28 kg, and this selected group for slaughter. No significant effect was observed with the use of supplementary sources of lipids on the loss of fasting, body weight at slaughter, empty body weight, hot carcass weight, cold carcass weight loss by cooling and biological yield. The non-carcass components, intestines and organs showed no differences across lipid additional sources. Regarding the fatty acid profile were observed 13 fatty acids, four of which are saturated, monounsaturated five-four polyunsaturated (PUFA). In proteome analysis, the proteins were expressed in greater quantity were located primarily at pH less than 5.5. Comparing the expression intensity spots between treatments can observe significant difference in the intensity of the spots 23 for the diet revealed fifteen proteins and of this total, seven were differentiated with respect to time. The proteins identified in this experiment can be mainly classified as structural cellular organization and protection to stress, as well as specific metabolic functions and other functions. The addition of various sources of lipid influenced the productive performance and features: hot carcass dressing and cold, yield and weight of the rack the weight and performance of the gastrointestinal tract filled, small intestine and liver income in Santa Ines sheep growing. Supplementation with different lipid sources influence the profile of fatty acids of Longissimus dorsi, so that diets containing FCC and Lcfa-Ca increased the amount of CLA in the muscle. The proteome analysis may be a method to identify marker proteins meat quality prediction. In this study, the identified proteins are highly relevant to the meat tenderness process, wherein the meat maturation process is complex and involves protein in different biological processes. The type of power had greater influence on the proportions of bodies responsible for digestion and absorption of nutrients.